Artefact-free Evaluation of Metal Enhanced Fluorescence in Silica Coated Gold Nanoparticles - Tânia Ribeiro (Nature Portfolio, 2017)
Abstract Metal nanoparticles can either quench or enhance the emission of dyes in their vicinity, but the precise measurement and understanding of this effect is still hindered by experimental artifacts, especially for particles in colloidal dispersion. Here, we introduce a new methodology to correct the inner filter effect of the metal on the dye emission. To test the method, we developed new hybrid nanoparticles with a gold core and a silica shell of precise thickness (tuned from 7 to 13 nm), with a high quantum yield perylenediimide dye on the surface. This novel approach effectively avoids fluorescence quenching, allowing us to measure emission enhancements of 5 to 30 times, with no change on the dye fluorescence lifetime. Being able to measure the emission enhancement in dye-metal hybrid nanoparticles in dispersion, free from inner filter and quenching artifacts, offers excellent prospects to guide the development of more efficient fluorescent probes, sensors and photonic devices.